Kontribusi Badan Permusyawaratan Desa terhadap Keterlibatan Warga dalam Program Penyuluhan Pembangunan di Kedaton, Kabupaten Bojonogoro - Ilham Aulia (Jurnal Inovasi dan Pengabdian, 2025)
This study aims to examine the contribution of the Village Consultative Body (BPD) in increasing community involvement in development outreach programs in Kedaton Village, Kapas District, Bojonegoro Regency. As a community representative institution at the village level, the BPD has an important role in bridging the aspirations of residents and the village government, especially in the participation-based development process. This research approach is qualitative descriptive with data collection techniques through interviews, observations, and documentation studies. The results of the study indicate that the BPD plays an active role in informing, educating, and mobilizing the community to participate in development outreach activities, both in the form of village deliberations, training, and open discussions. However, community involvement is still influenced by the level of awareness, time availability, and perceptions of the benefits of the program. Therefore, the BPD is required to be more proactive, innovative, and collaborative with village officials and community leaders in order to create participatory and sustainable village development.